Clinical comparison between conventional suture and vaporization with carbon dioxide laser in rat's skin - Paes-Jr, TJD; Niccoli, W. (Mary Ann Liebert, Inc., 2001)
Objective: This study compares wound healing efficiency on a rat's skin when the incision was closed with a conventional suture versus vaporized with a CO2 laser. Materials and Methods: In this study, 24 rats were used, and two longitudinal incisions were made with a conventional scalpel in the dorsum of each rat. The left incision was sutured with nylon thread, and the right incision was closed by vaporization with a defocused CO2 laser in continuous mode with an 8-watt power density. Clinical photographs were taken immediately after the procedure, 24 h later, and after 3, 7, 14, and 21 days, documenting the healing of the incision. Results: the results showed that there was an initial delay in wound repair in the vaporized incision as compared to the scalpel incision, but after 21 days, both incisions showed the same clinical characteristics. However, the vaporized incision showed no trauma of the tissue, as opposed to the sutured incision, and no hemorrhagic complications. Conclusion: These results suggest that the CO2 laser can eventually replace the use of sutures.